(3cfR GdeYGfi aj TQM MQR GdCeGfi hhLg GdJgGfis - (3HQgGf GdOjf CHh eMeO EHQGgje Hf YeQ Hf EHQGgje GdeDPf GdLYHQis; (3GdTGWHj GdebQF GdVQjQ , CHh eMeO,J (B590 (3g` s ((3EHQGgje Hf EHQGgje GdMfai s)
(3ChdgG (B:s
(3GdMeO ddg eHOi GdCee , hefTF GdPee , GdPi Yde HGdbde , Yde GdEfSGf eGde jYde , JfRg Yf GdEVOGO hGdCfOGO s
(3BNQgG (B:s
(3Gddge hGTQc ai HQcI OYGFi gPG ef HcdGeg ai gPG GdTQM GdeHGQc heTGjNi hPG bQGHJi hGdMeO ddg Je GdLRA GdKGfi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ Yf fSNI bQFJ hbhHdJ Ydi GdeUfa s
(3hYdjgG NWg s
(3YdjgG JUMjMGJ s
(3hcJHJ GdYfGhjjf HGdMeQI CHh HGdUaQI s
Keywords: (3GdbQGAGJ hGdJLhjOs